2016
DOI: 10.1002/tie.21796
|View full text |Cite
|
Sign up to set email alerts
|

Staged Development of Dynamic Capabilities: A Study of International Joint Ventures in India

Abstract: This article investigates the microfoundations of different stages of development of dynamic capabilities ( DCs ) in international joint ventures ( IJVs ). We conducted case-based research for three heterogeneous IJVs in the Indian life insurance space. Data collection involved detailed interviews and access to other archival data. Results offer interesting insights on (1) the process of the development of dynamic capabilities and (2) the relative importance of different stages in the development of dynamic ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 12 publications
(23 citation statements)
references
References 55 publications
0
19
0
Order By: Relevance
“…Another study conducted among SMEs (Borch & Madsen, ) developed several categories based on the dynamic capabilities literature, and confirmed the validity of external/internal integration and reconfiguration, learning networks, and resource‐acquisition capabilities. More recently, Roy and Khokle's () case study of international joint ventures identified the stages of sensing and sizing as fundamental in allowing firms to build dynamic capabilities, while reconfiguring/transforming was incorporated within seizing. In their case of the Chinese automotive industry, Guo, Jiang, and Yang () provide a different perspective to the development of dynamic capabilities.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Another study conducted among SMEs (Borch & Madsen, ) developed several categories based on the dynamic capabilities literature, and confirmed the validity of external/internal integration and reconfiguration, learning networks, and resource‐acquisition capabilities. More recently, Roy and Khokle's () case study of international joint ventures identified the stages of sensing and sizing as fundamental in allowing firms to build dynamic capabilities, while reconfiguring/transforming was incorporated within seizing. In their case of the Chinese automotive industry, Guo, Jiang, and Yang () provide a different perspective to the development of dynamic capabilities.…”
Section: Literature Reviewmentioning
confidence: 99%
“…There is sporadic research on the processes endemic in each country irrespective of the route it takes to internationalize. In one such study where the staged development of dynamic capabilities in IJVs was studied, it was found that successful IJVs in India have unique indigenous processes (Roy & Khokle, in press).…”
Section: Internationalization Of Indian Firmsmentioning
confidence: 99%
“…These researchers found that organizations from India that get involved in IJVs don't take proactive steps to develop dynamic capabilities (Roy & Khokle, in press), which has been conceptualized as the capability of an organization to speedily realign its capacities on realizing/perceiving a marked environmental change that has the potential to challenge the market position or existence of the organization (Barreto, ; Wang, Senaratne, & Rafiq, ; Wilhelm, Schlömer, & Maurer, ). There are two distinct stages in which the dynamic capabilities come into play; one is the sensing of the environment shift, and the other is the seizing of the market opportunity.…”
Section: Internationalization Of Indian Firmsmentioning
confidence: 99%
“…On the contrary, if the foreign partner collaborates with another domestic firm, terminated IJV partners will act as competitors. Reconfiguring a firms' external linkages as per the dynamic environment pertains to the dynamic capabilities view of strategic management (Dhir & Sushil, ; Eisenhardt & Martin, ; Helfat et al, ; Roy & Khokle, ; Teece, Pisano, & Shuen, ). In case of interaction after IJV termination, parent firms' ability to reconfigure their IJV to a supplier–buyer interaction or complementary interaction can be attributed to its dynamic capability.…”
Section: Introductionmentioning
confidence: 99%